Expression of CD8+ and Foxp3+ T Lymphocyte as Predictor for Response to Neoadjuvant Chemotherapy in Stage III Breast Cancer - I Nyoman Wawan Tirtha Yasa; I Wayan Sudarsa; I Wayan Niryana; Ni Putu Sriwidyani; I Made Jawi; I Wayan Putu Sutirta Yasa; Ida Bagus Tjakra Wibawa Manuaba; Ida Bagus Made Suryawisesa (The Indonesian Biomedical Journal, 2025)
BACKGROUND: Neoadjuvant chemotherapy (NAC) in breast cancer is usually utilized to eradicate micro-metastasis, induce apoptosis in tumor cells, and reduce the primary tumor size, enabling surgical intervention. Recent studies have shown that tumor-infiltrating lymphocytes (TILs), especially cytotoxic CD8+ T cells and immunosuppressive Foxp3+ regulatory T cells, influence tumor response to treatment. However, their role as predictive markers for NAC response remains unclear. Therefore, this study was performed to investigate whether high expression of CD8+ and low expression of Foxp3+ T lymphocytes are associated with better response to NAC in stage III breast cancer patients.METHODS: Total of 60 biopsy samples from stage III breast cancer patients were included, comprising 30 subjects in the response group (+) and 30 subjects in the non-response group (−). The expression levels of CD8+ and Foxp3+ T lymphocytes in tumor tissue were assessed semi-quantitatively by immunohistochemistry (IHC), using a scoring system based on the proportion and intensity of positively stained cells (Black’s grading criteria).RESULTS: Stage III breast cancer with high expression of CD8+ T lymphocytes was significantly associated with a better response to NAC (p=0.004; OR=6.882). Meanwhile, low expression of Foxp3+ T lymphocytes was not significantly associated with chemotherapy response (p=0.067; OR=3.250). A higher tumor grade was also associated with an improved response to treatment. The probability of achieving a positive response to NAC in subjects presenting with high CD8+ expression, low Foxp3+ expression, and high tumor grade was estimated at 96.98%.CONCLUSION: The combination of high expression of CD8+ T lymphocyte, low expression of Foxp3+ T lymphocyte and high tumor grade might be useful to predict good response to NAC in stage III breast cancer.KEYWORDS: CD8+ T lymphocyte, Foxp3+ T lymphocyte, neoadjuvant chemotherapy, breast cancer